The effect of Covid-19 epidemic on the industry of a Sub-Saharan Country: a perspective on sports industry in Nigeria - Gambo Adamu, Umar; Balatoni, Ildikó (METSZETEK Társadalomtudományi Folyóirat, 2022)
We investigated the impact of Covid-19 epidemic on the Nigerian economy and it’s Sports Industry. Thorough review of literature on empirical, conceptual, and theoretical studies on Covid-19 and Sports Economics was conducted. We examined the situation of Covid-19 and Sports Economics in Europe and America, and highlight the situation in Nigeria. Although scarce literature was found on the field of Sports Economics in the Nigerian context, over 60 articles were downloaded from recognized sources and analyzed in the field of Sports Economics and Covid-19 and careful selection of articles was made on recent and relevance basis and it is concluded that Covid-19 epidemic has negatively impacted global economies including that of Nigeria. The global Sports Economies including Nigeria was hard hit by the pandemic especially in terms of employment directly or indirectly considering the mono-economic nature of the Nigerian economy and incapacity of Sports Industry and Sports Economics in the country. It is however suggested, considering the huge potentials of the Sports Industry in Nigeria in job creation for youth and earnings that adequate funding/investment and aggressive transformation of the sector should be carried out.